2D Optoelectronics: Layer‐Dependent Optoelectronic Properties of 2D van der Waals SnS Grown by Pulsed Laser Deposition (Adv. Electron. Mater. 3/2020). (9th March 2020) - Wang, Weihao; Zhang, Tao; Seliverstov, Aleksandr; Zhang, Huihui; Wang, Yichen; Wang, Fengzhi; Peng, Xiaoli; Lu, Qiaoqi; Qin, Chao; Pan, Xinhua; Zeng, Yu‐Jia; Van Haesendonck, Chris; et al.
Abstract : In article number 1901020, Xinhua Pan, Yu‐Jia Zeng, Chris Van Haesendonck, and co‐workers successfully grow 2D layered tin monosulfide (SnS) by pulsed laser deposition. They demonstrate how the properties of SnS depend on the number of monolayers. This study sheds light on the layerdependent properties of 2D SnS, a material that promises to be important in 2D optoelectronic devices.